Adverse effects of hydroxyethyl starch (HES 130/0.4) on intestinal barrier integrity and metabolic function are abrogated by supplementation with Albumin. Issue 1 (December 2016) - Wong, Yuk; Lautenschläger, Ingmar; Zitta, Karina; Schildhauer, Christin; Parczany, Kerstin; Röcken, Christoph; Steinfath, Markus; Weiler, Norbert; Albrecht, Martin
Abstract Background Volume resuscitation with hydroxyethyl starch (HES) is controversially discussed and we recently showed that HES perfusion impairs endothelial and epithelial intestinal barrier integrity. Here we investigated whether Albumin containing HES solutions are superior to HES alone in maintaining intestinal barrier function. Methods An isolated perfused model of the mouse small intestine was used to investigate the effects of: (i) 3 % Albumin (Alb), (ii) 3 % HES or (iii) 1.5 % HES/1.5 % Albumin (HES/Alb). Intestinal morphology, cell damage, metabolic functions, fluid shifts and endothelial/epithelial barrier permeability were evaluated. Potentially involved signaling mechanisms (Erk1/2, Akt and Stat5 phosphorylation) were screened. Results HES induced histomorphological damage (p < 0.01 vs. Alb), by trend elevated the amount of luminal intestinal fatty acid binding protein and reduced galactose uptake (p < 0.001 vs. Alb). Luminal and lymphatic flow rates were increased (p < 0.001 vs. Alb), while vascular flow was decreased (p < 0.001 vs. Alb) during HES perfusion. HES also increased the vascular to luminal FITC-dextran transfer (p < 0.001 vs. Alb), pointing towards a fluid shift from the vascular to the luminal and lymphatic compartments during HES perfusion. Addition of Alb (HES/Alb) reversed all adverse effects of HES (p < 0.05 vs. HES), restored barrier integrity (p < 0.05 vs. HES) and improved metabolic function of the intestine (p < 0.001 vs. HES; p < 0.05 vs. Alb). Mechanistically, HES/Alb perfusion resulted in an increased phosphorylation of Erk1/2 and Akt kinases (p < 0.001 vs. HES), while Stat5 remained unchanged. Conclusions Albumin supplementation abrogates the adverse effects of HES in the intestine and underlying mechanism may function via phosphorylation of Erk1/2 and Akt. Albumin containing HES solutions are superior to HES alone and may improve the suitability of HES in the clinic.